2019
DOI: 10.30539/iraqijvm.v43i2.536
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Molecular Detection of Pseudomonas aeruginosa Isolated from Bovine Mastitis

Abstract: This study aimed to isolate Pseudomonas aeruginosa from cattle (bovine) milk with mastitis to characterize its antimicrobial susceptibility against some antibiotics, and to identify aminoglycoside acetyltransferase (aac-3-Ib) gene.A total of 100 bovine milk samples were collected randomly from different local cow farms at districts of Wasit governorate, Iraq. Six P. aeruginosa isolates were obtained using bacterial culture method and further identified by Analytical Profile Index (API-20E). The antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…For oxidative fermentation, the isolates were positive only for mannitol sugar and negative for other tested sugars. Similar results were previously described by (Carter and Wise, 2004;Al-Taee et al, 2019;Reetha et al, 2020) reported that 16 P. aeruginosa biotypes utilized galactose, mannose, and mannitol and displayed a green pigment and showed β hemolysis on blood agar with colony of green tinged with metallic sheen on cetrimide media. Furthermore, (Quinn et al, 2015;Al-Ruaby et al, 2022) applied the analytical profile index (API-20E) for biochemical testing of six P. aeruginosa isolates recovered from bovine mastitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For oxidative fermentation, the isolates were positive only for mannitol sugar and negative for other tested sugars. Similar results were previously described by (Carter and Wise, 2004;Al-Taee et al, 2019;Reetha et al, 2020) reported that 16 P. aeruginosa biotypes utilized galactose, mannose, and mannitol and displayed a green pigment and showed β hemolysis on blood agar with colony of green tinged with metallic sheen on cetrimide media. Furthermore, (Quinn et al, 2015;Al-Ruaby et al, 2022) applied the analytical profile index (API-20E) for biochemical testing of six P. aeruginosa isolates recovered from bovine mastitis.…”
Section: Discussionsupporting
confidence: 90%
“…However, the misuse and abuse of antibiotics is strongly related to the development of antibiotic resistance against various antimicrobial groups (Schwarz et al, 2018). The rapid emerging of various resistant P. aeruginosa isolates of bovine origin against aminoglycosides antibiotics referred to the presence of the aac(3)-Ib gene (Al-Taee et al, 2019). Furthermore, most strains of P. aeruginosa of bovine mastitis contain a type III secretion system that prompt an increase in the number of somatic cells count as well as the biofilms production that reducing the efficacy of antibiotics (Park et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Chandra et al 24 recorded that 40.7% strains were resistant to Streptomycin. Moreover, 100% of P. aeruginosa strains were resistant to Nalidixic acid, similar to the results of Al Samarrae et al 25 . Regarding Chloramphenicol, the resistance was 78.3%, in accordance with Imanah et al 26 ,and Mohammadpour et al 27 who recorded resistance to Chloramphenicol were 80%, and 97%, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…A total of10 antibiotics belonging to six antimicrobial classes were used in the analysis. The most of P. aeruginosa isolates showed multidrug resistance to all type of antibiotics as recorded in Table (3). This was in contact with a similar study in Egypt (El-Sha i, 2016) reported that the most P. aeruginosa isolates showed multidrug resistance to 17 types of antibiotic with resistance rate 25%-100%.The tested isolates showed resistance for quinolone, aminoglycosides, polypeptides sulphonamides, Lincomides, and β lactams groups.…”
Section: Resultssupporting
confidence: 79%